INDONESIAN EFL STUDENTS’ SELF-EFFICACY TOWARD LEARNING ACHIEVEMENT (A CASE STUDY OF THE YEAR INTAKE 2017 OF PBI 1.2) - Abdul Muis Said; Indah Miftah Awaliah; Riskan Wijayanti (International Conference on Social and Islamic Studies, 2021)
This research is aimed to find out how the self-efficacy impact Indonesian EFL learners’ learning achievement. This research has one research that is: “How does the self-efficacy impact the Indonesian EFL learners’ learning achievement”. This research was conducted at the Alauddin State Islamic University of Makassar. The subjects were six students of English Education Department of the year intake 2017 of PBI 1.2. The method used in this research was the qualitative research with employed a case study design. The instrument used to gather the data was interview guidelines to explore the sources of self-efficacy. Data of interview were analyzed based on procedure of data analysis that consisted of the data condensation, data display, and drawing conclusion / data verification. The results of this research showed that students who have high index achievement have high self-efficacy, judging by their confidence in answering questions and viewed from the sources of self-efficacy students who have high index achievement have high self-efficacy in mastery experiences and physiological states. Students who have middle index achievement have high self-efficacy because they have high confidence in answering questions. and viewed from the source of self-efficacy students who have middle index achievement have high self-efficacy in vicarious experiences and physiological states. Students who have low index achievement have low self-efficacy because they do not have high confidence in their ability to answer questions. So, students who have low index achievement have low self-efficacy in mastery experiences and physiological states. Based on the findings, the researcher recommends that it is important to the students to identify their self-efficacy because self-efficacy is essential for learners to facing the problems in academic colleges. Also, students with high levels of academic self-efficacy are more likely to persist at challenging academic tasks and put effort to achieve success in academic college, while students with low self-efficacy tend to give up easily and not confident of being able to perform given assignment.